PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMP NEGERI 1 TUHEMBERUA - ZEGA, RIDAWATI; LASE, NATALIA KRISTIANI; TELAUMBANUA, DESMAN; HAREFA, AGNES RENOSTINI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2024)
This research is motivated by the low learning outcomes of students in science subjects and the implementation of learning process activities is still teacher-centered. This research aims to: (1) Describe the implementation of the learning process through the application of the Numbered Head Together type cooperative learning model. (2) Describe the learning outcomes of students in science subjects through the application of the Numbered Head Together type cooperative learning model. The research location is at SMP Negeri 1 Tuhemberua. The research subjects were 22 class VIII students consisting of 8 boys and 14 girls. The type of research used is Classroom Action Research which consists of 4 stages, namely: (1) Planning, (2) Action, (3) Observation, and (4) Reflection. The research instruments used were: (1) Observation sheet, (2) Test of student learning outcomes, (3) Interview guide sheet. Research results: (1) Implementation of science learning process activities through the implementation of the Numbered Head Together type cooperative learning model obtained an average reflection result in Cycle I namely 57,29% with poor criteria and in Cycle II namely 84,34% with good criteria. (2) The learning outcomes of students in science subjects through the application of the Numbered Head Together type cooperative learning model obtained an average value of learning outcomes in Cycle I namely 70,68 with sufficient criteria and in Cycle II namely 83,41 with good criteria. ABSTRAKPenelitian ini dilatarbelakangi oleh rendahnya hasil belajar peserta didik pada mata pelajaran IPA dan pelaksanaan kegiatan proses pembelajaran masih berpusat kepada guru. Penelitian ini bertujuan untuk: (1) Mendeskripsikan pelaksanaan proses pembelajaran melalui penerapan model pembelajaran kooperatif tipe Numbered Head Together. (2) Mendeskripsikan hasil belajar peserta didik pada mata pelajaran IPA melalui penerapan model pembelajaran kooperatif tipe Numbered Head Together. Lokasi penelitian di SMP Negeri 1 Tuhemberua. Subjek penelitian adalah peserta didik kelas VIII dengan jumlah 22 orang yang terdiri dari 8 orang laki-laki dan 14 orang perempuan. Jenis penelitian yang digunakan adalah Penelitian Tindakan Kelas (Classroom Action Research) yang terdiri dari 4 tahap yaitu: (1) Perencanaan, (2) Tindakan, (3) Observasi, dan (4) Refleksi. Instrumen penelitian yang digunakan yaitu: (1) Lembaran observasi, (2) Tes hasil belajar peserta didik, (3) Lembaran panduan wawancara. Hasil penelitian: (1) Pelaksanaan kegiatan proses pembelajaran IPA melalui penerapan model pembelajaran kooperatif tipe Numbered Head Together diperoleh rata-rata hasil refleksi Siklus I yaitu 57,29% dengan kriteria kurang dan di Siklus II yaitu 84,34% dengan kriteria baik. (2) Hasil belajar peserta didik pada mata pelajaran IPA melalui penerapan model pembelajaran kooperatif tipe Numbered Head Together diperoleh nilai rata-rata hasil belajar di Siklus I yaitu 70,68 dengan kriteria cukup dan di Siklus II yaitu 83,41 dengan kriteria baik.